2000
DOI: 10.1006/mcne.2000.0843
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQ Polymorphism Influences Progression of Demyelination and Neurologic Deficits in a Viral Model of Multiple Sclerosis

Abstract: The importance of genetic susceptibility in determining the progression of demyelination and neurologic deficits is a major focus in neuroscience. We studied the influence of human leukocyte antigen (HLA)-DQ polymorphisms on disease course and neurologic impairment in virus-induced demyelination. HLA-DQ6 or DQ8 was inserted as a transgene into mice lacking endogenous expression of MHC class I (β 2 m) and class II (H2-A β ) molecules. Following Theiler's murine encephalomyelitis virus (TMEV) infection, we asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…The use of CD4 and CD8 knockout mice confirms this finding [56]. This is in contrast to the infection of double deficient Aβ 0 .β2m 0 mice, which fail to clear the acute virus encephalitis and die possibly before demyelination occurs in the spinal cord [48]. In the present experiment, the disease in Aβ 0 .β2m 0 .Hβ2m + .A11 + and Aβ 0 .β2m 0 .Hβ2m + .B27 + mice was similar to the established model.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The use of CD4 and CD8 knockout mice confirms this finding [56]. This is in contrast to the infection of double deficient Aβ 0 .β2m 0 mice, which fail to clear the acute virus encephalitis and die possibly before demyelination occurs in the spinal cord [48]. In the present experiment, the disease in Aβ 0 .β2m 0 .Hβ2m + .A11 + and Aβ 0 .β2m 0 .Hβ2m + .B27 + mice was similar to the established model.…”
Section: Discussionsupporting
confidence: 55%
“…Previous experiments performed with Aβ 0 .β2m 0 mice demonstrated that these mice die of overwhelming virus-induced encephalomyelitis within 16 to 18 dpi with TMEV [48]. We infected Aβ 0 .β2m 0 mice ( N  = 25) with TMEV, and mice were either moribund or dead by 18 dpi.…”
Section: Resultsmentioning
confidence: 99%
“…Immunocytochemistry was performed on paraffin-embedded sections as previously described (27). Slides were deparaffinized in xylene and rehydrated through an ethanol series (absolute, 95, 70, and 50%).…”
Section: Methodsmentioning
confidence: 99%
“…The subsequent disease course depends decisively upon the genetic background of the used mice strain. Thus, while the virus is eliminated in resistant C57BL/6 mice after the initial phase, an inadequate antiviral immune response leads to prolonged viral infection in susceptible SJL/J mice [2,3,4]. Hereby, viral antigen-induced delayed-type hypersensitivity and myelin-specific autoimmunity induce inflammatory demyelination predominantly in the spinal cord of susceptible mice strains, resembling the chronic progressive form of MS.…”
Section: Introductionmentioning
confidence: 99%